Dimorphic Jumper Maevia inclemens (Walckenaer 1837) (Arachnida: Araneae: Salticidae) - Laurel Lietzenmayer; Lisa Taylor (EDIS)
Maevia inclemens is a common jumping spider found in vines and ivy along tree lines throughout eastern North America. Learn about this interesting and possibly agriculturally beneficial spider in this 3-page fact sheet written by Laurel Lietzenmayer and Lisa Taylor and published by the UF/IFAS Department of Entomology and Nematology. http://edis.ifas.ufl.edu/in1209